Implementation of Business Intelligence for Data Visualization at PT PP London Sumatra Indonesia - Lubis, Muhammad Ali; Tania, Ken Ditha (Sistemasi: Jurnal Sistem Informasi, 2024)
This research project examines the deployment of Business Intelligence (BI) utilising Tableau to enhance data visualisation at PT PP London Sumatra Indonesia Tbk, with a particular focus on the palm oil processing and sales sector. Palm oil is a significant commodity in the Indonesian economy. This study highlights the significance of accessing accurate data in order to inform business decisions. The implementation of Business Intelligence (BI) facilitates the processing of data from disparate sources into informative visualisations, thereby enabling the identification of operational trends and patterns. The methodology comprised the collection of data on a daily basis, the cleansing of said data using ETL processes, and the presentation of the data in a visual format through Tableau. The results demonstrated an improvement in operational efficiency and a reduction in the time taken to make decisions, while also providing insights that could inform strategic decisions made by management. It is anticipated that this implementation will assist the company in meeting market challenges and improving product quality and business processes.